Morpho-Physiological, ISSR-Based Molecular Characterization of Gamma-Irradiated Soybean Under Waterlogging Stress - Solihah, Anisatus; Indahsari, Dianita; Mahendra, Belva Aria; Fadilah, Aulia Sunan; Muslihatin, Wirdhatul; Chokwiwatkul, Ratchata; Saputro, Triono Bagus (Universitas Negeri Semarang, 2025)
Soybeans (Glycine max) are Indonesia's third-most important food crop after rice and maize. However, because of its susceptibility to waterlogging, its productivity decreases. Gamma-ray irradiation has been used to create soybean varieties that are resistant to waterlogging. This study investigates the genetic variation and morpho-physiological traits of irradiated Grobogan soybean varieties under waterlogging stress. Soybean seeds were exposed to gamma-ray doses of 0 Gy, 25 Gy, 50 Gy, 75 Gy, and 100 Gy, then the soybean plants were submerged in water at concentrations of 0%, 100%, 150%, 200%, and 250%. The study's morpho-physiological parameters include seed weight, pod count, plant height, chlorophyll content, and seed viability. The results imply that varying waterlogging levels and radiation dosages show varied responses. All irradiation doses showed optimal growth in the control treatment, whereas 75 Gy and 100 Gy under 250% waterlogging conditions showed the most severe growth inhibition. To evaluate genetic variation among the irradiated soybean variants, five ISSR markers were employed. Because of its high PIC value of 0.391, marker ISSR-1 was found to be the most effective in detecting polymorphisms. ISSR-1 is a promising marker for assessing genetic diversity in irradiated soybean plants, according to the results. These results are valuable for the development of soybean breeding strategies targeting improved tolerance to waterlogging stress.